1981
DOI: 10.1073/pnas.78.11.7028
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of chromosomal genes in Streptococcus pneumoniae.

Abstract: A system for molecular cloning in Streptococcus pneumoniae was developed. The multicopy plasmids pMV158 (5.4 kilobases) and pLS1 (4.3 kilobases), which confer tetracycline resistance, were used as vectors to clone chromosomal genes of S. pneumoniae in host cells of this species. A 3.3-kilobase restriction fragment containing the maiM gene, which codes for amylomaltase, was cloned in a deletion mutant lacking chromosomal homology with the fragment. The recombinant plasmid, pLS70, could transform over 50% of a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0

Year Published

1982
1982
2003
2003

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 104 publications
(76 citation statements)
references
References 25 publications
2
74
0
Order By: Relevance
“…When crude sonicated extracts were obtained from the strains used in the experiments reported in Figs 3 and 4, we found ( Table 2) that the extracts obtained from M51 were about fivefold more active than those obtained from the tyt' strain when tested on purified, choline-labeled pneumococcal cell walls, whereas M31 and M32 (a frame-shift mutant of the lytA gene) completely lacked amidase activity [8]. The higher level of amidase activity found in M52 would be due to the presence of several copies of pRG2 per cell as previously found for the vector plasmid pLSl [16]. In fact we have found that M51 contains about 120 copies of pRG2 as compared to the 45 copies of pLSl found in M34.…”
Section: Biological Consequences Of the Presence Ojprg2 In M31mentioning
confidence: 71%
“…When crude sonicated extracts were obtained from the strains used in the experiments reported in Figs 3 and 4, we found ( Table 2) that the extracts obtained from M51 were about fivefold more active than those obtained from the tyt' strain when tested on purified, choline-labeled pneumococcal cell walls, whereas M31 and M32 (a frame-shift mutant of the lytA gene) completely lacked amidase activity [8]. The higher level of amidase activity found in M52 would be due to the presence of several copies of pRG2 per cell as previously found for the vector plasmid pLSl [16]. In fact we have found that M51 contains about 120 copies of pRG2 as compared to the 45 copies of pLSl found in M34.…”
Section: Biological Consequences Of the Presence Ojprg2 In M31mentioning
confidence: 71%
“…DNA fragments were separated by electrophoresis on agarose gels and purified by binding to glass milk, according to the specifications of the supplier of GeneClean (BIO-101, Inc.). The plasmid content of the clones was analyzed in alkaline lysates prepared by the method of Birnboim and Doly (3) for E. coli and by a modification of that method (37) for S. pneumoniae. Cultures of S. pneumoniae were grown and transformed as previously described (23).…”
Section: Methodsmentioning
confidence: 99%
“…Among the tools and methods developed in my laboratory, one of the most important was the pneumococcal cloning system using derivatives of the plasmid pMV158 (53). We were forced to turn to this system by our inability to clone many important pneumococcal genes, such as malM, endA, and hexA, in the available E. coli systems, apparently due to the strong promoters of S. pneumoniae and the toxicity of the gene products in E. coli (52).…”
Section: Cloning In Streptococcus Pneumoniaementioning
confidence: 99%